Cultural family care to diabetic patients who consumed alcohol and/or tobacco - Leticia Casique Casique; Teresita de Jesús Muñoz Torres; Blanca Yuliana Castro García; Zuleima Centeno González; Rodrigo López Franco (Universidad de Alicante, 2018)
Objective: Understand the cultural care provided by family to the diabetic patient consuming the alcohol and/or tobacco. Methodology: Analytical and qualitative study, we conducted analysis of speech, with a final sample of 9 subjects with Diabetes; the data collected from the survey "Cultural family care to diabetic patients who consumed alcohol and/or tobacco" to apply through a focus group. The personal data were analysed using the statistical package SPSS v.17.0 and the qualitative data were analyzed based on the Grounded of Data Theory. Results: The phenomenon found is an optimal and comprehensive family care, which manifests itself by an excellent behavioral expression and verbal, coupled with feelings of gratitude by the individual. Conclusion: The family care provided to diabetic patients an emotional, social, physical and spiritual level is essential to strengthen the provision in adherence to treatment, and to face the mourning by the loss of a lifestyle.